Islam, Kristen, dan Aruh: Agama Baru dan Perubahan Agroekosistem Peladang Dayak Loksado, Kalimantan - Soehadha, Moh. (Fakultas Ilmu Sosial dan Ilmu Politik UIN Walisongo Semarang, 2018)
This article focuses on the influence of new religions (Islam and Christianity) to the changing of agroecosystem in Dayak Loksado. In line with the government policy in employing modern agricultural farming, spreading new religions (Islam and Christianity) have affected the changing of traditional farming to the modern one. This research aims to know the influence of religious conversion in an agroecosystem in Dayak Loksado and several influential factors and also the impact of that system. Using qualitative as an approach, the data are collected from in-depth interview focused on special region named Balai Padang, Malinau, Loksado. The result of this research shows that conversion to a new religion has changed agroecosystem in Dayak Loksado in terms of belief and practice for some people. Moreover, swidden cultivation or nomad agriculture has changed into a permanent one gradually. There are several influential factors decreasing of a local field for paddies and availability of field for rubbers and palms plantations.